Gall Bladder complications of Typhoid - Bhandari, RS; Luitel, BR; Lakhey, PJ; Singh, KP (Journal of Institute of Medicine Nepal, 2010)
Surgical complications of typhoid fever usually involve gut but infrequently typhoid fever also involves gallbladder. Complications range from acalculous cholecystitis to perforation. We present a series of three cases which included acalculous cholecystitis, gangrenous cholecystitis and perforation of gallbladder. Investigations revealed them to be a complication of Enteric fever. Acalculous cholecystitis was managed conservatively; gangrenous cholecystitis and perforated gallbladder underwent emergency cholecystectomy. All three cases were discharged after treatment and are doing well on follow up. Key words: Gallbladder, perforation, typhoid The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, August, 2009; 31:2 44-47